Angioedema. Issue 4 (April 2017) - LoVerde, Daniel; Files, Daniel Clark; Krishnaswamy, Guha
Abstract : Objectives: Angioedema is a potentially life-threatening occurrence that is encountered by critical care providers. The mechanistic understanding of angioedema syndromes has improved in recent years, and novel medications are available that improve outcomes from these syndromes. This clinically focused review will describe the underlying genetics, pathophysiology, classification and treatment of angioedema syndromes, with an emphasis on the novel pharmacologic agents that have recently become available for acute treatment. Data Sources: A MEDLINE search was conducted with the MeSH terms angioedema, acquired angioedema, hereditary angioedema type III, and angiotensin converting enzyme inhibitor-induced angioedema. Study Selection: Selected publications describing angioedema, clinical trials, diagnosis, management, and genetics were retrieved (reviews, guidelines, clinical trials, case series), and their bibliographies were also reviewed to identify relevant publications. Data Extraction: Data from the relevant publications were reviewed, summarized and the information synthesized. Data Synthesis: The data obtained were used to describe the current state of diagnosis and management of various angioedema syndromes. Conclusions: Angioedema is a life-threatening syndrome with multiple subtypes, each with a distinct pathophysiology. We present an evidence-based approach to the diagnosis and suggested management of various subtypes of angioedema. Securing the airway remains the most important intervention, followed by administration of both established and more novel pharmacologic interventions based on disease pathology. Abstract : Supplemental Digital Content is available in the text.